How Much Snot is Too Much Snot? Community-Making Amid Pandemic Times in Early Childhood Education - Land, Nicole; Thomas, Andrea; Todorovic, Sanja; Sanders, Angélique (Alberta Journal of Educational Research)

(untitled) (Faculty of Education, University of Alberta, 2024)
This article details a pedagogical inquiry research project, Crafting Pedagogies with(in) Suspension: Viral Pedagogies in COVID times in Early Childhood Education, where educator co-researchers collaborated with a pedagogist-researcher to explore how we might craft early childhood education pedagogies relevant to pandemic times. In particular, we trace how questions of community-making emerged as quotidian conceptions of community failed in the conditions of the pandemic. Thinking with the question “how much snot is too much snot?”—a question educators were asked to assess as a marker of community participation—we share three tensions of community-making: policing bodies, normalcy, and community-making as an ongoing process. Importantly, we work to share our pedagogical thinking with these tensions, asking how they create different possibilities for making community with children and families in educational contexts.